2022
DOI: 10.31083/j.jin2104108
|View full text |Cite
|
Sign up to set email alerts
|

Too Much and Too Little: Antidepressant Treatment in Stroke Survivors during the First Year

Abstract: Background: Post-stroke depression (PSD) is the most frequent mental illness after stroke, affecting about 30% of stroke survivors and hampering rehabilitation outcome. While current guidelines recommend monitored antidepressant treatment (ADT) in PSD, the limited precision between the use and need of ADT in clinical practice remains underassessed and poorly understood. Methods: Depression according to DSM criteria and ADT was assessed in n = 294 stroke survivors from two German rehabilitation centers about on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…[ 36 , 37 ]. These data may explain the increased use of antidepressants found in this study (79.31%) compared to previous studies where they only represent 50% of diagnosed patients [ 38 ].…”
Section: Discussionmentioning
confidence: 41%
“…[ 36 , 37 ]. These data may explain the increased use of antidepressants found in this study (79.31%) compared to previous studies where they only represent 50% of diagnosed patients [ 38 ].…”
Section: Discussionmentioning
confidence: 41%
“…Because a discontinuation of antidepressant medication shortly after its start during an ongoing depressive episode is potentially harmful and may lead to further symptom aggravation, 63 existing antidepressant medication will not be changed or conditioned for randomised patients, but recorded and used as a covariate (see the ‘Statistical analysis’ section). With this procedure, the proportion of (pre)medicated patients and changes in regiments 17 can be estimated for a subsequent confirmatory definite trial.…”
Section: Design and Methodsmentioning
confidence: 99%
“…Open access survivors receive antidepressant drug treatment, and less than 10% receive psychotherapy treatment. [17][18][19] This striking gap is exacerbated by missing treatment guidelines and scarce evidence for standardised psychotherapy treatments for PSD. 11 Moreover, psychotherapists might be reluctant to treat PSD due to an uncertainty how to address stroke-specific challenges, handle medication and often complex comorbid somatic symptoms.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The optimal timing for PSD screening also remains unclear ( 8 ) as depression may occur up to several years after the stroke and shows a non-linear pattern of emergence ( 10 , 11 ). Previous evidence underlined the need for early identification of PSD risk factors, which represents a promising strategy to address the timing issue and improve treatment use in PSD, which is characterized by both over- and undertreatment ( 12 , 13 ). Moreover, meta-analytic evidence demonstrated that psychosocial interventions and pharmacotherapy are efficacious for prevention of depression after stroke, albeit with an increased risk of nausea and bone fracture for pharmacotherapy ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%